Human papillomavirus in women submitted to oncotic colpocytology - Noronha, Vânia; Cruz, Ermelinda Moutinho da; Naum-Pinho, Cecília; Mello, Wyller; Noronha, Rodolfo; Silveira, Ígor; Mendes, Sandro; Villa, Luísa (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: human papillomavirus is the main risk accepted for development of malignant lesions in the uterine cervix. Objective: verify the prevalenceof HPV and the purpose of having a better knowledge of the role of HPV and other co-risk factors for development of cancer and precursory lesions in theuterine cervix. Methods: 491 women from 30 to 45 years old were studied that looked for screening of cervical cancer in the Maternal Children OutpatientUnit of the University of Pará, from September, 2001 to September, 2002. Patients were submitted to collection of cervical material for cytological analysisat Central Laboratory of Public Health. DNA was extracted from the samples at Evandro Chagas Institute. Polymerase Chain Reaction and genotypesprocedures by reverse hybridization were carried out at Ludwig Institute of Cancer Research São Paulo – SP. Patients with cytological diagnosis of ASCUS/AGUS, LSIL and HSIL were included in group A and patients with cytology results in the range of normality in group B. Results: total prevalence of HPV was12,6%. According stratification, 44,1% (26/59) to group A and 8,3 % (36/432) to group B. HPV types considered of high risk were detected in 39% of womenin the group A (23/59), being 28% (13/46) with ASCUS, 71% with LSIL (5/7) and 83% with HSIL (5/6); and in 4,4% (19/432) in the group B. Among the sub-group infected from the group A and from the group B, HPV of high risk was present respectively in 88,5% (23/26) and 52,8% (19/36). HPV 16 was the mostfrequent, being detected in 30,8% (8/26) of the infected women of group A and in 8,3% (3/36) of infected women of group B. There were significant associationsof prevalence of HPV, HPV of high risk, and HPV type 16 in women from group A. Among co-risk factors, first intercourse at early age was significant associatedwith patients with cytological diagnosis of ASCUS/AGUS, LSIl e HSIL (representative women from group A). Other variables had no significant association.Conclusion: the discovered facts are coherent with several researches of world and national literature, as well as several researches the prevalence of HPV asthe present types smear of specimes from the uterine cervice of women from North region of Brazil.